Autoimmune Diseases Contributing Factors, Specific Cases of Autoimmune Diseases, and Stem Cell and Other Therapies - Chan, James (IntechOpen, 2012)
Autoimmune disease represents a group of more than 60 different chronic autoimmune diseases that affect approximately 6% of the population. Autoimmune diseases arise when ones immune system actively targets and destroys self tissue resulting in clinical disease with prime examples such as Lupus and Type 1 diabetes. The immune system is designed to protect us from foreign pathogens such as viruses and bacteria. However, during the process of generating immune cells for this purpose, as a negative consequence, self-reactive immune cells are also generated. This book aims to present the latest knowledge and insights regarding the different contributing factors and their interplay, discussions on several autoimmune diseases and their case studies, and therapeutic treatments, including stem cell, for autoimmune diseases.